The impact of the Ar-Rahnu service quality on customer’s satisfaction at Bank Kerjasama Rakyat Malaysia Berhad, Seremban / Nur Syafinaz Abd Wahid - Abd Wahid, Nur Syafinaz (Faculty of Business and Management, 2011)
The purpose of this research is to know the impact of the Ar-Rahnu service quality on customer’s satisfaction at Bank Kerjasama Rakyat Malaysia Berhad, Seremban. Bank Kerjasama Rakyat Malaysia Berhad not only provide Ar-Rahnu service but other services such as personal loans, car loans, housing loans, education loans and so forth for making customers easier while they come to Bank Rakyat. Although the services are to make customers easier while they come to Bank Rakyat but they are some complaints from the customers about the service quality for example such operating hours not convenience, the communication between staff and customers and so on. The main objectives of this research is to identify the level of customer satisfaction toward Ar-Rahnu service quality that has been provided by Bank Rakyat, the level of service quality provide by the Ar-Rahnu towards their customers and to identify the most factors that influence the customer satisfaction of Ar- Rahnu service that have been offered to them. This research is conducted by using non probability sampling and the sampling method is convenience sampling. 40 respondents have been asked by using questionnaires in order to gain information and feedback to the company. The questionnaires consist of question about the service quality dimensions and customers satisfaction toward the Ar-Rahnu service at Bank Rakyat Seremban. The findings showed that most of the customers were satisfied with the service provided at Bank Rakyat Seremban. Although the customers satisfied with the service, the company need to improve and maintain the service quality if they want to build long term relationship with their customers.